Tilgivelsens teologi i Det Gamle Testamente - Lomholt, Carl (Dansk Teologisk Tidsskrift, 2015)
This paper studies the Old Testament’s conception of forgiveness, which is characterized by its one-sidedness. According to the almost unambiguous testimony of the OT literature, only God can forgive. However, it is important to see God’s unreserved forgiveness against the background of his resentment at the apostasy and sin of man. At the same time the OT also weights God’s punishment and grace in favour of his grace. The paper also discusses the few OT examples of human forgiveness, noting them as remarkable exceptions which confirm the main thesis of the one-dimensional aspect of forgiveness. This aspect is due to the fact that the OT does not know the incarnation of God. It is not until the New Testament that there is a necessary connection between God’s forgiveness and the willingness of man to forgive his neighbour.